Two-dimensional gel electrophoretic detection of protein carbonyls derivatized with biotin-hydrazide - Wu, Jinzi (J Chromatogr B Analyt Technol Biomed Life Sci, 2015)
Protein carbonyls are protein oxidation products that are often used to measure the magnitude of protein oxidative damage induced by reactive oxygen or reactive nitrogen species. Protein carbonyls have been found to be elevated during aging and in age-related diseases such as stroke, diabetes, and neurodegenerative diseases. In the present article, we provide detailed protocols for detection of mitochondrial protein carbonyls labeled with biotin-hydrazide followed by 2-dimensional isoelectric focusing (IEF)/SDS-PAGE and Western blotting probed with horse-radish peroxidase-conjugated streptavidin. The presented procedures can also be modified for detection of carbonylation of non-mitochondrial proteins.